KEEFEKTIFAN MODEL PEMBELAJARAN RECIPROCAL TEACHING BERBANTUAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI KEBIASAAN BELAJAR: Array - Febriani, Rizka Nanda; Ponoharjo, Ponoharjo; Oktaviani, Dian Nataria (Universitas Peradaban, 2019)
The purpose of this study was to describe: 1) mathematical problem-solving abilities of students taught with Reciprocal Teaching learning models assisted by Student Activity Sheet that had met the minimal completeness criteria. 2) students' mathematical problem solving abilities taught using the Reciprocal Teaching model assisted by Student Activity Sheet are better than those taught using conventional models. The population in this study were all eighth grade students in the even semester of SMP Negeri 4 Brebes in the academic year 2017/2018. Sampling uses Cluster Random Sampling. Samples taken 1 class as an experimental class, 1 class as a control class, and 1 class as a trial class. Data collection methods used documentation, observation and tests. Analysis of the data used by setting a significance level of 5% is the test of the proportion of one right-hand side, the t-test of the right-hand side and the anova of two lines, with the prerequisite test namely the normality test and the homogeneity test.